Efektivitas Ekstrak Daun Ubi Jalar (Ipomea batatas) Terhadap Tingkat Stres Induk Ikan Nila (Oreochromis niloticus) dalam Sistem Transportasi - Nurussalam, Wildan; Maksum, Ahmad; Supriyono, Eddy; Mahmud, Moh Burhanuddin; Permatasari, Sheny (Universitas Batangahari Jambi, 2025)
Broodstock transportation is a critical phase in aquaculture in Nile tilapia (Oreochromis niloticus), directly influencing brood quality and reproductive success. This study investigated the effectiveness of sweet potato leaf extract (Ipomoea batatas) at varying concentrations in a closed transport system to reduce stress and improve survival. A completely randomized design (CRD) with four treatments and three replications was employed: N1 (control, no extract), N2 (2 mL/L extract), N3 (4 mL/L extract), and N4 (6 mL/L extract). Parameters measured included survival rate (SR), daily growth rate (DGR), feed consumption (FC), water quality (temperature, pH, dissolved oxygen, ammonia, nitrite), and stress response via blood glucose levels. Results indicated that adding sweet potato leaf extract significantly influenced water quality, reduced stress, and improved fish survival. The 4 mL/L treatment (N3) yielded the best outcomes, with a 100% survival rate and the lowest blood glucose level (77.67 mg/dL), suggesting its potential as an effective natural antistress agent during broodstock transport.